Impact of dark triad personality traits on turnover intention and mental health of employees through cyberbullying - Rimsha Baheer; Kanwal Iqbal Khan; Zeeshan Rafiq; Tayyiba Rashid (Cogent Business & Management, 2023)
The increased usage of technology has engendered different forms of bullying. While scholars affirm that cyberbullying is considered to exhibit the most harmful impacts on individuals among the different types of bullying. It needs to be underscored that the multifaceted and recurring nature of cyberbullying, particularly in the workplace, has a more hazardous effect on employees. It is urged that the highly competitive working environment has exacerbated the problems of rivalry among employees, which subsequently pushes them towards cyberbullying. Despite an extensive body of knowledge on traditional bullying, research still lacks the effect of cyberbullying in the workplace context. This research addresses the gaps by explaining the impact of the dark triad of personality traits (DTPT) on turnover intention and employees' mental health through cyberbullying. It incorporated a unique multistage sampling approach in which data were gathered through self-administered questionnaires from the banking sector. The analyses showed a direct relationship between the DTPT and turnover intention. Cyberbullying partially mediates the relationship between DTPT and turnover intention. Findings also indicate that the DTPT negatively affects employees' mental health. A vital facet of this research is testing the mediating role of cyberbullying between DTPT and employees' mental health and turnover intention. The findings are of great value to organizational stakeholders, where management can adopt various strategies and training programs to reduce the detrimental effects of cyberbullying. Such initiatives enable employees to cope with mental health issues, mitigating negative workplace behaviour and minimizing turnover intention.
Keywords: D23; 650; turnover intention; technology; Dark triad of personality traits; machiavellianism; mental health; narcissism; psychopathy; workplace behaviour